Evidence of Solomon and Sheba? (Biblical archaeology review, 2023)
The article offers news about an intriguing archaeological discovery of a small inscription in Jerusalem's Ophel excavations, which, according to scholar Daniel Vainstub, may provide evidence of trade connections between ancient South Arabia and Jerusalem during King Solomon's era.